Clinicopathological correlation of p63 in Urothelial Carcinoma: Immunohistochemical Study - Kaur, Rupinderjit; Manjari, Mridu; Piplani, Sanjay (Annals of Pathology and Laboratory Medicine, 2020)
Background: Urothelial cancer (UCa) poses a significant medical and public health concern in most parts of the world and is defined as a pan- urothelial disease in which entire urothelium of the renal pelvis to the urethra can undergo malignant transformation. Bladder tumors account for 90–95% of urothelial carcinomas and are the most common urinary tract malignancy. It is three times less common in females. Methods: The study was conducted on 40 cases of Urothelial Carcinoma received as biopsy specimens in a tertiary care hospital. There were 20 cases each of low grade and high grade and after grading these were subjected to p63 expression. Result: 78% of the patients were from 50-75 year age group with Male to Female ratio being 4:1. Painless hematuria was most common complaint. The size varied from 0.5 to 7.2 cm. For P63, 38 (95%) cases showed positive p63 expression. Of which 20 cases were low grade and 18 (90%) were high grade papillary urothelial carcinomas. Of P63 positive cases 36 cases showed moderate to strong staining intensity whereas two cases showed mild staining intensity. The p63 expression decreased with grade and invasion. Conclusion: P63 immunoexpression decreases with increasing grade of tumor as well as with invasion thus showing that its expression is related with good prognosis.